Strategies for improving friction behavior based on carbon nanotube additive materials. (December 2022) - Gu, Yunqing; Ma, Longbiao; Yan, Muhan; He, Chengdong; Zhang, Junjun; Mou, Jiegang; Wu, Denghao; Ren, Yun
Abstract: In order to develop materials with better tribological properties using carbon nanotubes (CNTs) as additives in the future, this paper reviews the research status and improvement mechanism of the tribological properties of materials based on CNTs as additives. Firstly, the unique spatial structure and properties of CNTs are analyzed to investigate the feasibility of using carbon nanotubes as an additive material to improve tribological properties. Secondly, the effects of CNTs as additive materials on friction coefficient and wear performance and the factors affecting the improvement effect are presented from different perspectives (size effect, structure effect, concentration effect, dispersion effect, individual effect, synergistic effect) in lubricants and coatings. Finally, future research on the application of CNTs in tribology is prospected. Graphical Abstract: ga1 Highlights: The structural characteristics and classification of carbon nanotubes are reviewed. Four factors affecting the improvement effect of carbon nanotubes on lubricant. Effects of individual and synergistic effects on the tribological properties of coatings.